Personalized medical support for young athletes after splenectomy - N. S. Tsetsema; Iu. K. Uspenskaia; S. V. Matveev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2024)
Introduction. The relevance of the problem is determined – an increase in the number of patients who underwent splenectomy, in the absence of currently developed methodological (clinical) recommendations on admission to training and competitive events.The objective was to develop criteria for admission to training and competitive events, to determine the frequency and volume of medical examinations for this category of persons.Methods and materials. The analysis of the sources of domestic and foreign authors on the management of patients after splenectomy was carried out. We collected the detailed life history, disease history, sports history, information about family history for the development of diseases of the cardiovascular system, gastrointestinal tract, hematopoietic organs, analysis of the hospital discharge summary, data evaluation from laboratory and instrumental studies (particularly, ultrasound examination of the abdominal organs), ECG with exercise, exercise tests (Martinet-Kushelevsky) in two athletes who underwent splenectomy due to various reasons (blunt abdominal trauma, the spleen rupture in athlete A. N., 14 years old, microspherocytic hemolytic Minkowski-Choffard anemia complicated by sepsis in athlete N. V., 12 years old). The functional fitness indicators taking into account the sports training stage, the results of medical and pedagogical observations during the training process before and after surgery were assessed.Results. In the clinical blood analysis of athlete A. N., there was a slight leukocytosis (leukocytes- 10.94∙109/l), thrombocytosis (platelets – 669∙109/l), no changes in erythron, erythrocytes- 5.46∙1012/l, hemoglobin – 136 g/l, hematocrit – 42.3 %, neutrophils – 4.53∙109/l, lymphocytes – 5.33∙109l. Leukocyte formula by microscopy was without significant pathological changes. The diagnosis was confirmed as: “Reactive thrombocytosis. Condition after splenectomy”. According to the results of IME, there were no absolute contraindications to training and competitive football activities. The athlete received a medical certificate of admission to training and competitive events. In the clinical blood analysis of athlete N.V., there was: erythrocytes – 5.44∙1012/l, hemoglobin – 163 g/l, hematocrit – 44.4 %, leukocytes – 12.2∙109/l, neutrophils – 3.8∙109/l, lymphocytes – 6.4∙109/l, platelets – 515∙109/l. He was taken to the regular medical check-up of a hematologist with the diagnosis: “Hereditary spherocytosis, hemolysis compensation. Condition after splenectomy”. Due to the absence of absolute contraindications for training and competitive football events, the athlete was issued the medical certificate on admission to training and competitive events.Conclusion. A splenectomy history is not an absolute contraindication to sports. The management of an athlete after splenectomy requires an individual approach, taking into account age, sport and stage of sports training, the presence of chronic diseases and/or changes in physical, instrumental and laboratory studies.